2012
DOI: 10.1115/1.4006609
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurements of Ingestion Through Turbine Rim Seals—Part I: Externally Induced Ingress

Abstract: This paper describes a new research facility which experimentally models hot gas ingestion into the wheel-space of an axial turbine stage. Measurements of the CO2 gas concentration in the rim-seal region and inside the cavity are used to assess the performance of two generic (though engine-representative) rim-seal geometries in terms of the variation of concentration effectiveness with sealing flow rate. The variation of pressure in the turbine annulus, which governs this externally-induced (EI) ingestion, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 16 publications
10
33
1
Order By: Relevance
“…The effectiveness in the front wheel-space (location D in Fig. 7) and at the purge hole radius in the rim cavity (location C) exhibited behavior that deviated from the previously measured effectiveness curves [11,21,25], like that shown for the outer radius in the rim cavity (location B). The data shown for location B were similar to the previous effectiveness curves for which the orifice model was derived, and it will be shown later that the model fits the data well.…”
Section: Sealing Effectiveness For Purge Flowcontrasting
confidence: 52%
See 1 more Smart Citation
“…The effectiveness in the front wheel-space (location D in Fig. 7) and at the purge hole radius in the rim cavity (location C) exhibited behavior that deviated from the previously measured effectiveness curves [11,21,25], like that shown for the outer radius in the rim cavity (location B). The data shown for location B were similar to the previous effectiveness curves for which the orifice model was derived, and it will be shown later that the model fits the data well.…”
Section: Sealing Effectiveness For Purge Flowcontrasting
confidence: 52%
“…Similar to the research of Clark et al [17,18], partial span airfoils were used for this study to reduce the mass flow requirements while maintaining an engine-relevant axial Reynolds number, rotational Reynolds number, and Mach number. Other researchers have also proven the use of partial span airfoils for studying rim seals and ingestion [20][21][22].…”
Section: Description Of Facility and Turbinementioning
confidence: 99%
“…Sangan et al [17] used the Bath orifice model to derive the so-called effectiveness equations that express e, the sealing effec tiveness, in terms of ®n, the nondimensional sealing flow rate. For El ingress, 3>o ____________£__________ ®min,£/ " [1 + Tc -2/3(1 -g)2/3]3/2…”
Section: Brief Review Of El Ingressmentioning
confidence: 99%
“…Their results revealed that the mass flow rate of the ingression flow depends strongly on the rim seal configuration, and a specific rim seal geometry led to the reduction of hot gas ingestion into the rim seal. Sangan et al [5,6] experimentally studied the sealing performances of two types of rim seal, i.e., single and double radial rim seals, under the stationary and rotating conditions. They found that the rotating cases show better sealing performances than the stationary cases.…”
Section: Introductionmentioning
confidence: 99%